Grid Interconnected Photo Voltaic System Using Shunt Active Filter for Power Quality Improvement - Kala Rathi; N. Rathina Prabha (Institute of Advanced Engineering and Science, 2018)
Now-a-days, power generation and utilization became more complicated which further affects the economy of a country. The available non-renewable energy sources that supply the demanded power do not consider environmental challenges like global warming and pollution. This leads to the development of power generation based on Renewable Energy Resources (RES). These RES are connected to the grid through power electronic converters which offer countless power quality issues that must be rectified to deliver a quality power to the end users. The proposed work uses a three phase Voltage Source Inverter (VSI) based Shunt Active Power Filter (SAPF) fed by solar Photo Voltaic (PV) system to eliminate current harmonics at the source side of the grid. The output of the PV system is given to a boost converter along with self–lift single-ended primary-inductor converter (SEPIC) for supplying high voltage gain which is accompanied by a Perturb & Observe Maximum Power Point Tracking (MPPT).The main objective of this paper is to eliminate the current harmonics at the grid side using SAPF. Also, the proposed SAPF is used for exporting the power generated from PV to the grid. The overall system performance is validated with a help of MATLAB/SIMULINK.